1971
DOI: 10.2172/4042967
|View full text |Cite
|
Sign up to set email alerts
|

Work Plan for Continuation of the Project ''Reduction of Atmospheric Polution by the Application of Fluidized-Bed Combustion.''

Abstract: U.S. A t o m i c Energy C s m m i s s i o n a n d t h e ENVIRONMENTAL PROTECTION AGENCY AIR QUALITY OFFICE DIQSSLON OF CONTROL S Y S T E M S ARGONNE NATIONAL LABORATORY DISCLAIMERThis report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency Thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1975
1975
1975
1975

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is often held that, because of their low operating temperatures, fluidized beds would produce little nitric oxide (5,6,12,13). But some previous studies (7, [14][15][16][17][18][19][20] have suggested that local temperatures may be much higher than the average bed temperature, and that nitric oxide may be produced from fuel-bound nitrogen as well as from atmospheric nitrogen. Jonke et al (17)(18)(19) we studied the combustion of propane-air mixtures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is often held that, because of their low operating temperatures, fluidized beds would produce little nitric oxide (5,6,12,13). But some previous studies (7, [14][15][16][17][18][19][20] have suggested that local temperatures may be much higher than the average bed temperature, and that nitric oxide may be produced from fuel-bound nitrogen as well as from atmospheric nitrogen. Jonke et al (17)(18)(19) we studied the combustion of propane-air mixtures.…”
mentioning
confidence: 99%
“…But some previous studies (7, [14][15][16][17][18][19][20] have suggested that local temperatures may be much higher than the average bed temperature, and that nitric oxide may be produced from fuel-bound nitrogen as well as from atmospheric nitrogen. Jonke et al (17)(18)(19) we studied the combustion of propane-air mixtures. Nitric oxide emission was studied first as the bed parameters were varied.…”
mentioning
confidence: 99%